Modified silicone rubber for fabrication and contacting of flexible suspended membranes of n-/p-GaP nanowires with a single-walled carbon nanotube transparent contact. Issue 11 (14th February 2020) - Neplokh, Vladimir; Kochetkov, Fedor M.; Deriabin, Konstantin V.; Fedorov, Vladimir V.; Bolshakov, Alexey D.; Eliseev, Igor E.; Mikhailovskii, Vladimir Yu.; Ilatovskii, Daniil A.; Krasnikov, Dmitry V.; Tchernycheva, Maria; Cirlin, George E.; Nasibulin, Albert G.; et al.
Abstract : Rubber materials are the key components of flexible optoelectronic devices, especially for the light-emitting diodes based on arrays of inorganic nanowires (NWs). Abstract : Rubber materials are the key components of flexible optoelectronic devices, especially for the light-emitting diodes based on arrays of inorganic nanowires (NWs). This paper reports on polydimethylsiloxane- graft -polystyrene (PDMS-St) as a new flexible substrate of GaP NW array structures. The NWs were encapsulated by the newly introduced G-coating method to substitute the inefficient mainstream spin-coating. To further exploit the flexibility and the stretchability of the NW/PDMS-St structures, the ferrocenyl-containing polymethylhydrosiloxane was synthesized and successfully used as an electrode for the NWs. In order to make an alternative highly efficient transparent electrode, a new application of conductive single-walled carbon nanotubes was demonstrated. The novel materials and methods demonstrated unsurpassed mechanical stability of the fabricated flexible electronic devices.